Dorsal and Ventral Stream Function in Children With Developmental Coordination Disorder - Micheletti, Serena; Corbett, Fleur; Atkinson, Janette; Braddick, Oliver; Mattei, Paola; Galli, Jessica; Calza, Stefano; Fazzi, Elisa (Frontiers in Human Neuroscience, 2021)
Dorsal stream cortical networks underpin a cluster of visuomotor, visuospatial and visual attention functions. Sensitivity to global coherence of motion and static form is considered a signature of visual cortical processing in the dorsal stream (motion) relative to the ventral stream (form). Poorer sensitivity to global motion compared to global static form has been found across a diverse range of neurodevelopmental disorders, suggesting a ‘dorsal stream vulnerability’. However, previous studies of global coherence sensitivity in Developmental Coordination Disorder (DCD) have shown conflicting findings. We examined two groups totalling 102 children with DCD (age 5 -12 years), using the ‘Ball in the Grass’ psychophysical test to compare sensitivity to global motion and global static form. Motor impairment was measured using the Movement-ABC (M-ABC). Global coherence sensitivity was compared with a typically developing control group (N=69) in the same age range. Children with DCD showed impaired sensitivity to global motion (p=0.002), but not global form (p=0.695), compared to controls. Within the DCD group, motor impairment showed a significant linear relationship with global form sensitivity (p<0.001). There was also a significant quadratic relationship between motor impairment and global motion sensitivity (p=0.046), where poorer global motion sensitivity was only apparent with greater motor impairment. We suggest that two distinct visually related components, associated with global form and global motion sensitivity, contribute to DCD differentially over the range of severity of the disorder. Possible neural circuitry underlying these relationships is discussed.